Altered Temporal Dynamics of the Amplitude of Low-Frequency Fluctuations in Comitant Exotropia Patients - Chen, Ri-Bo; Ye, Shu-Yuan; Pei, Chong-Gang; Zhong, Yu-Lin (Frontiers in Human Neuroscience, 2022)
Abstract Purpose: Comitant exotropia (CE) is a common eye movement disorder. Growing evidences reported that CE patients were accompanied by changes in brain function. However, dynamic time-varying of neural activity changes in CE patients remains unknown. Methods: A total of thirty-six CE patients (25 males and 11 females) and thirty-six well-matched healthy controls underwent magnetic resonance imaging (fMRI) scanning. The dynamic amplitude of low-frequency fluctuation (dALFF) with sliding window method was applied to investigate the dynamic neural activity changes in CE patients Results: compared with HCs, CE patients showed significantly decreased dALFF values in the right superior parietal lobule (SPL) and right precuneus gyrus(PreCUN). Moreover, We found that the dALFF maps showed an accuracy of 48.61% and area under curve of 0.54 for distinguishing the CE patients from HCs. Conclusion: our study demonstrates that CE patients showed altered dynamic neural activity changes in the right SPL and right PreCUN, which might be mirror the neuropathological mechanism of stereoscopic dysfunction in CE patients.